Formation of intercultural competence of foreign languages through the system of higher education - Khalilovа, Shahnoza; Халілова, Шахноза (Східноєвропейський національний університет ім. Лесі Українки, 2016)
The current amplitude of globalization and the degree of constant interaction between people with different mentalities and from different cultures points up the importance of gaining experience in the area of intercultural competence. For teachers of foreign languages, developing competence in this field has become one of the main components of their activities. Theoretical reviews of research on this subject and summaries of the achievements of scientists suggest that for future foreign language teachers, the acquisition of experience leading to intercultural competence cannot be obtained using traditional approaches to the problems of their personalities. For the work of students and university teachers, this situation leads to a perpetual block in adapting to the progressive processes of international cultures, because it is not possible to learn a foreign language in a manner t hat is completely detached from the corresponding foreign culture, or which fails to identify the linkage of that culture with others. I n the article the formation of intercultural competence of future teachers of foreign languages, reveals the main princi ples, objectives and concept of improving intercultural competence of students of pedagogical profile have also been analyzed. Інтенсивна глобалізація та постійна взаємодія людей з різним менталітетом і культурою диктує сьогодні важливість досвіду міжкультурної компетентності. Для викладачів іноземних мов саме ця компетентність має стати одним із головних компонентів їх діяльності. Теоретичний огляд наукових досліджень з даного питання та узагальнення досягнень вчених дозволяють зробити висновок, що створення досвіду міжкультурної компетентності майбутніх викладачів іноземної мови не вписується в традиційні підходи до проблеми становлення їх особистості. Така ситуація генерує постійний розрив роботи студентів і викладачів вищої школи з прогресивними процесами світової культури, адже не можливо вивчати іноземну мову зовсім відірвано від іноземної культури або не пов’язуючи свою культуру з іншою. Відтак в статті аналізується формування міжкультурної компетентності майбутніх учителів іноземної мови, розкриваються основні принципи, завдання та концепції вдосконалення міжкультурної компетентності студентів педагогічного профілю.
Формування міжкультурної компетентності майбутніх учителів іноземної мови в системі вищої освіти
Keywords: designing and rebuilding educational reality; creativity; emotional and value relationships; objectintercultural; social and intercultural competence; intercultural autokompetentsiya; moral and aesthetic standards of conduct; проектування і перебудова педагогічної дійсності; творча діяльність; емоційно-ціннісні відносини; предметно-міжкультурна і соціально-міжкультурна компетентності; міжкультурна аутокомпетенція; морально-естетичні норми поведінки